Analysis of influencing factors of serum SCCA elevation in 309 CAP patients with normal CEA,NSE and CYFRA21-1 - Wang, Jinghan; Tang, Xiao; Liu, Xin; Zhang, Jing (Frontiers in Oncology, 2024)
Introduction: Squamous cell carcinoma antigen (SCCA) is one of the auxiliary diagnostic indicators of lung squamous cell carcinoma,and an increase in serum SCCA can predict the occurrence of lung squamous cell carcinoma. However,whether SCCA is also elevated in pneumonia patients without malignancy is still not clear.Therefore,we studied influencing factors of elevated serum SCCA in patients with community-acquired pneumonia.: We retrospectively enrolled 309 patients who were admitted to the Respiratory department with normal serum Carcinoembryonic antigen (CEA),Neuronspecific enolase (NSE),and Cytokeratin 19 fragment (CYFRA21-1) level and were diagnosed with community-acquired pneumonia (CAP). The patients' serum SCCA level,body temperature, age,sex,white blood cell (WBC) count,hypersensitive C-reactive protein (Hs-CRP) level,and serum amyloid A (SAA) were recorded. Logistic regression models were used to analyze the risk factors of SCCA elevation. The dose-response relationship between temperature and risk of SCCA increase was analyzed using Restricted cubic splines (RCS).Results: Of the 309 patients,143(46.3%) showed elevated SCCA levels.The logistic regression analysis revealed a significant influence of age and body temperature on elevated SCCA (P<0.05) levels. For every one-year increase in age,the probability of elevated SCCA decreased by 3% [OR=0.97,95%CI:0.95,0.99].For every 1℃ increase in body temperature, the risk of elevated SCCA increased by 2.75 times [OR=3.75,95%CI:2.55,5.49].The patients were sorted into quartiles based on body temperature. Compared with patients in the Q1 of body temperature group,patients in the Q3 group were at 7.92 times higher risk [OR=7.92, 95%CI:3.27,19.16].and the risk of elevated SCCA was increased by 22.85 times in the Q4 group [OR=23.85,95%CI:8.38,67.89] after adjusting for age,gender,Hs-CRP,SAA,and WBC. RCS analysis showed there was a linear relationship between temperature index and risk of elevated SCCA.In summary,for CAP patients with normal CEA,NSE and CYFRA21-1 level,age and body temperature are influencing factors of SCCA elevation.Higher body temperature has a strong association with the occurrence of SCCA elevation.